An investigation into cultural differences in the conceptualization of and attributions about cognitive decline in the elderly - Fair, David Alan (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
There is little data regarding the prevalence of dementia in South Africa. Estimating such prevalence is problematic as the most commonly used cognitive screening tests are inappropriate for use in non-western populations. For this reason researchers have explored the use of informant questionnaires where relatives provide information on cognitive functioning over the last year. In the South African context Lenger, de Villiers & Louw (1996) conducted a dementia case-ascertainment study in a Xhosa-speaking community near Cape Town using a well-known informant questionnaire, the DECO, and concurrent clinical assessment. Reflecting on the discrepancies between DECO scores and clinical diagnosis, the researchers conducted interviews to explore beliefs and expectations regarding the elderly and cognitive decline. The aims of the current research were to gather comparative data from Bothasig, an English-speaking community, in order to explore areas of commonality and difference in perceptions and attributions regarding cognitive decline in the elderly. The study found that a significant percentage of informants from both Bothasig and Langa consider forgetfulness to be normal in old age. Different discourses around illness in the elderly were identified incorporating a range of medicalised and folk attributions. The discussion showed that informant perceptions within the Langa community may increase the likelihood that observational data provided in informant questionnaires may be confounded by cultural perceptions regarding the elderly. In addition, certain items on the DECO were found to be unsuitable for use across groups and modifications were proposed. The data was analyzed using both quantitative methods and phenomenological discourse analysis. The discussion concluded with metatheoretical reflections on the tension between etic and emic perspectives in cross-cultural research.
Keywords: Dementia; Older people; Dementia -- Case studies